Additive manufacturing of polyetheretherketone and its composites: A review. Issue 9 (6th August 2022) - Francis, Justy N.; Banerjee, Indranil; Chugh, Ankita; Singh, Jaiveer
Abstract: Polyetheretherketone (PEEK) is a high‐performance plastic with favorable physical, mechanical, chemical, and biological properties for various industrial applications. Most PEEK substrates/components are manufactured using traditional methods like milling, compression molding, injection molding, pressure sintering, and so forth. With the advent of various additive manufacturing (AM) techniques, researchers have been working on optimizing the processing parameters for AM of PEEK. Furthermore, several PEEK composites with improved properties have also been developed, and efforts have also been made to use these PEEK composites in AM. Since AM of PEEK and its composites is a relatively new area of the advanced manufacturing process, the field faces many challenges. There is a dearth of comprehensive reports on this topic. Keeping this perspective in mind, we have tried to collate the relevant information on the composites and AM of PEEK in this review. The review highlighted the influence of variation in composition on material properties and performance of PEEK and showed the correlation with AM processability of such composites. A detailed analysis of the various reports on fused deposition modeling and selective laser sintering based processing of PEEK composites is included in the review. Critical barriers to the AM of these high‐performance polymer composites are pointed out. We have also included the outcome of some interesting studies about the coating of PEEK with various materials/compounds to provide a broader perspective. This review will help the researcher to design and develop additively manufactured PEEK‐based structures with improved and customized properties. Abstract :